But It Did Sink, You Understand What I Mean’: Topography of the Titanic - Emma Grey (Review of Irish Studies in Europe)
While post-Agreement Belfast has been undergoing an urban facelift, characterised by numerous modern property developments, tourist-centric initiatives and a general desire to eradicate the negative elements of the past with the aim of making Belfast a better place for the future, there has been a failure to address the real problems of segregation and socio-economic divide within post-conflict Belfast. This article looks at how Kai-Olaf Hesse’s Topography of the Titanic exposes some of the major flaws and lacunae in the city’s regeneration programme.